Teachers’ Strategies in responding students’ Minor Misbehavior (a Case Study in SMP Negeri 26 Samarinda) - Siti Halimah; Rinda Fitriana; Ariyanti Ariyanti (Borneo Educational Journal (Borju), 2019)
This Study aimed to find out: (1) What students’ minor misbehavior appears in the classroom? (2) What strategies do teachers use to response the students’ minor misbehavior? This research used a qualitative study with case study design. The study involved the English teacher, 7th and 8th grade students on SMPN 26 Samarinda. Data were collected by observation class. To check the reliability of the data, triangulation was also used in this research. The researcher compared the accrued information with different relevant researchers and consulted the lectures implicated in the study.   The findings showed that the common students' minor misbehavior that appeared in the class were: talking each other, clowning around, drumming, tapping a pen, sleeping, and daydreaming. Moreover, to responding the misbehavior, the teacher used a various strategy that were: ignoring, reminder in soft voice, calling on the student, public rule reminder, the look, facial expression, proximity and warning the consequence.